2021
DOI: 10.1016/j.jbc.2021.101051
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional protein 4.1R regulates the asymmetric segregation of Numb during terminal erythroid maturation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…In adult brain and pituitary gland, immune and hematopoietic system, on average both exon 9 and exon 3 inclusion level is lower than 25%, suggesting that the p65 (Ex9sk & Ex3sk) Numb isoform is predominantly expressed (Table 1). These observations are consistent with previously observed changes in both exon 9 and exon 3 inclusion during development measured using RT-PCR or protein expression: rat and human brain (Verdi, Bashirullah et al 1999, Dooley, James et al 2003, Bani-Yaghoub, Kubu et al 2007, mouse pituitary gland (Moran, Goldberg et al 2011), rat auditory epithelium (Gao, Chi et al 2011), and human and mouse erythroid cells (Huang, Vu et al 2021).…”
Section: Resultssupporting
confidence: 93%
“…In adult brain and pituitary gland, immune and hematopoietic system, on average both exon 9 and exon 3 inclusion level is lower than 25%, suggesting that the p65 (Ex9sk & Ex3sk) Numb isoform is predominantly expressed (Table 1). These observations are consistent with previously observed changes in both exon 9 and exon 3 inclusion during development measured using RT-PCR or protein expression: rat and human brain (Verdi, Bashirullah et al 1999, Dooley, James et al 2003, Bani-Yaghoub, Kubu et al 2007, mouse pituitary gland (Moran, Goldberg et al 2011), rat auditory epithelium (Gao, Chi et al 2011), and human and mouse erythroid cells (Huang, Vu et al 2021).…”
Section: Resultssupporting
confidence: 93%
“…Recently, Huang et al suggested that 4.1R regulates the asymmetric segregation of the Notch signaling regulatory protein Numb during terminal erythroid maturation. They also identified a critical role for 4.1R in mediating erythropoiesis [25].…”
Section: Cell Divisionmentioning
confidence: 99%
“…Consequently, these depletions notably increase the proportion of symmetric distribution of Numb. Knockdown of 4.1R reduces the size of Numb in the daughter cells and enhances Notch signaling, directly promoting cell proliferation and delaying cell maturation [25].…”
Section: Cell Fate Regulationmentioning
confidence: 99%
“…Thus, rather than simply being a regulatory or even a structural protein, we posit that BAG3 serves as a universal glue that selectively localizes proteins to specific cellular domains as well as to partner proteins [ 12 ]. While not common, there are examples of this type of protein multi-tasking: the multi-functional protein 4.1R being a good example [ 13 ].…”
Section: Introductionmentioning
confidence: 99%